Wady wrodzoneModified Norwood operation in a neonate with a double inlet left ventricle, transposition of the great arteries, hypoplastic right ventricle, left aortic arch and the right subclavian artery branching off the descending aorta. A case report - Kołcz, Jacek; Skalski, Janusz H. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
The Norwood operation with various variants of the pulmonary-systemic shunts is presently successfully performed in newborns with hypoplastic left heart syndrome (HLHS). The most commonly employed modifications include the right Blalock-Taussig shunt (RBTS) and the right ventricle-to-pulmonary artery shunt (RV-PA). The report presents a modification of the Norwood procedure employed in a newborn with a double inlet left ventricle, transposition of the great arteries, hypoplastic right ventricle, left aortic arch and the right subclavian artery branching off the descending aorta. Due to the anatomical variant of the defect, the classic reconstruction of the aortic arch was performed with a homogeneous pulmonary artery patch, while the pulmonary-systemic shunt was achieved using a polytetrafluoroethylene graft interposed between the right pulmonary artery branch and the reconstructed ascending aorta strengthened by glutaraldehyde-fixed autogenous pericardium patches. The Norwood operation with some slight technical modifications may be used in an increasing spectrum of single ventricle type congenital heart defects as the preliminary stage of palliative treatment before the hemi-Fontan and Fontan operations.